Emociju regulācijas saistība ar uztverto sociālo atbalstu un vecāka kompetences izjūtu pirmsskolas vecuma bērnu mātēm - Šleža, Gerda (Latvijas Universitāte, 2025)
Šī bakalaura darba mērķis bija izpētīt saistības emociju regulācijai ar uztverto sociālo atbalstu un vecāka kompetences izjūtu pirmsskolas vecuma bērnu mātēm. Pētījumā piedalījās 61 pirmsskolas vecuma bērnu māte. Pētījuma dalībnieki bija pilngadīgas sievietes, ar vismaz vienu bērnu vecumā no 2 līdz 7 gadiem. Pētījumā izvēlētās metodes bija aptaujas: emociju regulācijas noteikšanai (Emotion Regulation Questionnaire – ERQ (Gross & John, 2003)) ; uztvertā sociālā atbalsta noteikšanai ( Multidimensional Scales of Perceived Social Support (Zimet, Dahlem & Farley, 1988)); vecāka izjūtas noteikšanai (Parenting Sense of Competence Scale, (PSOC),(Johnston & Mash, 1989)). Demogrāfisko datu noskaidrošanai tika ievākti dati par dzimumu, vecumu, izglītību, bērna vecumu, bērnu skaitu pirmskolas vecumā un bērna dzimumu. Pētījumā secināts, ka pastāv statistiski nozīmīgas pozitīvas saistības uztvertajam sociālajam atbalstam ar vecāka kompetences izjūtu pirmsskolas vecuma bērnu mātēm. No significant relationship was found for emotion regulation, despite the significant relationship between percieved social support and parental competence among mothers of preschool-aged children.

This bachelor's thesis investigated the relationships between emotion regulation, perceived social support, and parental sense of competence among mothers of preschool-aged children. The study included 61 mothers of preschool-aged children. Participants were adult women with at least one child aged 2-7 years. The study employed three questionnaires: the Emotion Regulation Questionnaire (ERQ) (Gross & John, 2003) to assess emotion regulation; the Multidimensional Scales of Perceived Social Support (Zimet, Dahlem & Farley, 1988) to measure perceived social support; and the Parenting Sense of Competence Scale (PSOC) (Johnston & Mash, 1989) to assess parental sense of competence. Demographic data on gender, age, education level, child's age, number of preschool-aged children, and child's gender were also collected. The findings revealed statistically significant positive correlations between perceived social support and parental sense of competence among mothers of preschool-aged children. Emotion regulation remained consistent regardless of variations in perceived social support and parental sense of competence.
The Relationship Between Emotion Regulation, Perceived Social Support, and Parental Competence in Mothers of Preschool-Aged Children
Keywords: Psiholoģija; emociju regulācija; uztvertais sociālais atbalsts; vecāka kompetences izjūta; pirmsskolas vecuma bērnu mātes